Editorial: Circular Business Models and Strategies—The Key to Sustainable Business and Innovative Supply Chains - Sehnem, Simone (2022)
The concept of circular economy has recently emerged as a political goal (Gregson et al., 2015), in a context of rising resource prices and climate change. However, the idea is more often criticized, questioned than celebrated. In a circular economic model, waste becomes a resource to be recovered and revalued through recycling and reuse. In this context, five circular economy models are emerging and spreading rapidly in organizations, namely: circular supply chains, recovery and recycling, product life cycle extension, shared platforms and product as a service (Lacy and Rutqvist, 2015). However, companies looking to adopt these circular models will have to develop new business models at the expense of linear thinking (Sehnem et al., 2022). Such models help companies to improve differentiation, in reducing costs, in generating new revenues, in reducing risks as well as in reducing the impact on the supply of virgin resources. The adoption of these five circular business models has grown substantially in the past decade, although there are still many perspectives for change. Initially, innovation via the circular business model was driven by start-ups. Now, large multinationals are also making grandiose moves. While advancing the narrative of circular economy, multiple supply chain members need to adapt processes, practices and behaviors to implement sustainable business models (Morali and Searcy, 2013). Circular business models are used to regenerate materials, retain the value of resources and contributes to the re-signification of natural ecosystems and the reduction of waste and pollution. Despite this comprehension, the literature lacks for information on how this affects sustainable business and innovative supply chains. The circular economy encourages the use of clean energy, the use of cascading resources and has the potential to generate sustainable solutions at micro, meso and macro levels.